2021
DOI: 10.1111/1346-8138.16210
|View full text |Cite
|
Sign up to set email alerts
|

Annular plaques mimicking Rowell’s syndrome in the course of coronavirus disease 2019 mRNA vaccines: An overlooked phenomenon?

Abstract: Effective vaccines for prevention of severe course and lethal outcome of coronavirus disease 2019 have been developed and approved in regulatory rolling and fast‐track procedures; they are now widely distributed worldwide. Data about cutaneous side‐effects of the new mRNA‐type vaccines is scant, however. We herein report two similar cases of cutaneous adverse drug reactions (ADR) mimicking Rowell’s syndrome that occurred after the first dose of BNT162b2 and mRNA‐1273, respectively. Both patients achieved promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Another study divided the skin side effects of the MRNA12-73 vaccine into early and late (on average after eight days). Contrary to the discussed patient, most of the less common skin complications, such as lesions larger than 10 cm, also appeared late [16,25].…”
Section: Discussioncontrasting
confidence: 63%
“…Another study divided the skin side effects of the MRNA12-73 vaccine into early and late (on average after eight days). Contrary to the discussed patient, most of the less common skin complications, such as lesions larger than 10 cm, also appeared late [16,25].…”
Section: Discussioncontrasting
confidence: 63%
“…Table 1 [ 8 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] and Table 2 [ 39 40 41 42 43 44 ] presents the results obtained from evaluation of 31 eligible articles retrieved from the databases.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the reported case, the puffiness of the hands began within 12 h. Niebel D. et al (2021) reported severe joint pain, skin symptoms similar to lupus erythematosus, fatigue, and vomiting, but no fever, after MRNA12-73 vaccine intake in a 22-year-old female patient with hypothyroidism. The test results and lack of family history of lupus erythematosus made the specialists attribute these symptoms to corona vaccination [21]. Another study divided the skin side effects of the MRNA12-73 vaccine into early and late (on average after eight days).…”
Section: Discussionmentioning
confidence: 99%